Model Optimalisasi Pelayanan Reservasi Pada Rumah Sakit Bali Jimbaran - Ayu Candra Ariningsih, Ni Made; Cahya Dewi, Kadek (Fakultas Ekonomi Universitas Gresik, 2023)
The rapid development of health and information technology requires the health sector to rely on information technology to provide fast and appropriate services to the community. A good information management system has been proven to reduce error rates, improve system quality, and reduce diagnostic errors. Hospitals as public service providers need to implement an efficient information management system to improve performance and service. One important component in the healthcare system is the reservation system. This study aims to optimize reservation services at Bali Jimbaran Hospital by designing an online reservation system. Through the R&D method, researchers design an integrated and efficient information system to improve service quality. The result of this study is a reservation service optimization model that pays attention to user needs and factors that affect users. This model will help improve service quality, management efficiency, and economic value for hospitals.